The prognostic significance of K-ras, p53, and APC mutations in colorectal carcinoma. Issue 9 (20th April 2005) - Conlin, A; Smith, G; Carey, F A; Wolf, C R; Steele, R J C
Abstract : Background: Accumulation of molecular alterations, including mutations in Kirsten-ras (K-ras), p53, and adenomatous polyposis coli (APC), contribute to colorectal carcinogenesis. Our group has previously characterised a panel of sporadic colorectal adenocarcinomas for mutations in these three genes and has shown that p53 and K-ras mutations rarely occur in the same colorectal tumour. This suggests that mutations in these genes are on separate pathways to colorectal cancer development and may influence patient prognosis independently. Aims: To correlate the presence or absence of mutations in K-ras, p53, and APC with survival in a cohort of colorectal cancer patients. Patients: A series of 107 inpatients treated surgically for colorectal cancer in Tayside, Scotland between November 1997 and December 1999. Methods: Colorectal tumours were characterised for mutations in K-ras, p53, and APC. Kaplan-Meier survival curves were constructed using overall survival and disease specific survival as the primary end points. Patient survival was analysed using the log rank test and Cox proportional hazards model. Results: Patients with K-ras mutations had significantly poorer overall survival than patients without K-ras mutations (p = 0.0098). Multivariate analysis correcting for Dukes' stage, age, and sex confirmed this (hazard ratio 2.9 (95% confidence interval 1.4–6.2); p = 0.0040). K-ras mutations were also significantly associated with poorer disease specific survival. The presence of APC and p53 mutations did not affect survival in this cohort of patients (p = 0.9034 and p = 0.8290, respectively). Conclusions: Our data indicate that the presence of K-ras mutations predicts poor patient prognosis in colorectal cancer, independently of tumour stage.